Evaluation of the efficacy and safety of transplantation of adipose-derived stem cells in the treatment of refractory fistulizing Crohn's disease (Research, Society and Development, 2022)
Aim: The treatment of perianal fistulas in Crohn's disease (CD) is a challenge. Adipose-derived stem cells (ADSCs) are an option for treating fistulas, but their behavior at the injection site still needs to be further investigated. The efficacy and safety of autologous transplantation of ADSCs of patients with refractory perianal fistulizing CD was evaluated. Method: A total of 6 patients (18-48 years) were recruited. The intervention was three applications of autologous ADSCs (total of 3x107 cells). The evaluations happened in the 12th and 24th week after the first application, been considered primary and secondary efficacy outcomes, safety outcomes, anthropometric and food quality assessments. Results: Three patients completed the study and been treated 8 fistulas with ADSCs, none application-related effect was observed. The healing closure of the external part occurred in four fistulas, with local reepithelialization, and also two closed completely in the 12th week. The Van Assche index indicates improvement in only one of the patients. On the other hand, the Clinical Perianal Disease Activity Index and the quality of life assessment indicated progress for the three patients until the end of the study. By the CD Simple Endoscopic Score, two patients had the disease endoscopically inactive at the end of follow-up. Most of the anthropometric measurements were adequate and the foods that had low consumption throughout the study, in conformity for the three evaluated, were those belonging to the group of beans. Conclusion: It is concluded that autologous ADSCs have clinical potential to safely treat refractory perianal fistulizing CD.